5′UTR +24T>C CR2 is not associated with nasopharyngeal carcinoma development in the North Region of Portugal. (23rd February 2016) - Sousa, H; Bastos, MJ; Ribeiro, J; Oliveira, S; Breda, E; Catarino, R; Medeiros, R
Abstract : Objective: We have analysed the association of the +24T>C polymorphism (rs3813946) in CR2, the cellular receptor for Epstein–Barr virus (EBV), in the susceptibility for the development of nasopharyngeal carcinoma (NPC). Methods: A retrospective case–control study was developed with peripheral blood samples from 111 individuals with NPC and 608 healthy individuals (controls) from the North region of Portugal. The genotyping analysis was performed by allelic discrimination real‐time PCR using a TaqMan ® SNP Genotyping Assay. Results: The genotype distribution was 62.2% TT, 34.2% TC and 3.6% CC for NPC patients; and 65.0%, 30.6% and 4.4%, respectively, for controls. Our study showed no statistical association between the genotype distribution in controls and all types of NPC ( P  = 0.717); nevertheless, the analysis showed statistically significant differences ( P  = 0.038) regarding cases with well‐ or moderately differentiated types of NPC suggesting that +24CC/CT genotypes are associated with increased risk (OR = 4.16; 95% CI 1.28–15.7; P  =   0.016). Conclusions: This is the first study in Western populations to characterize the association of the CR2 +24T>C polymorphism in NPC development, and our results suggest that more studies are required to clarify the impact on NPC susceptibility in different populations.